Complementary and Alternative Medicine as a Functional Tendency. Formation of Preferences, Agency, and Diffusion Among Citizenships - Perez, Antonia Ramirez (European Scientific Journal, ESJ, 2016)
The work is centered in the social analysis of the formation of preferences and in the description of the social action related with the complementary and alternative medicine (CAM). The theoretical framework that will help to show this generation of preferences is the fashion theory and the social tendencies theory. And to illustrate this reality it has been get an empirical body of information from the Seville city, Spain, as case study. The mixed methodology used allows to show the narrative of the process as well as the ’pictures’ in particular moments. To the first objective, it has been carried out ethnographic fieldwork from a decade. To the second objective, it has been elaborated a database with the complementary and alternative medicine activities offered in Seville. Both methodologies help to show a map of this disruptive innovation and the shape adopted. The results show that CAM tendency emerges because it is useful to the society. Beyond the seasonal fashions, the irruption of this disruptive fashion indicates a process of social change with a new understanding of the health. In the CAM the preferences are generated for instrumental and axiological reasons, though it seems that axiological rationality would be a powerful explanation when we observe its emergence. And finally the results show a group of innovative people as the agents of the change. Moreover, they would seem to be the group that accelerate the process until the tipping point, from which the trend expands thanks to the processes of mimesis or contagion.